Minimal clinically important differences for the EQ-5D and QWB-SA in Post-traumatic Stress Disorder (PTSD): results from a Doubly Randomized Preference Trial (DRPT) - Le, Quang A (BioMed Central, 2013)
OBJECTIVE: To determine the minimal clinically important difference (MCID) for the health-utility measures EuroQol-5 dimensions (EQ-5D) and Quality of Well Being Self-Administered (QWB-SA) Scale in PTSD patients. RESEARCH DESIGN AND METHODS: Two hundred patients aged 18 to 65 years with PTSD enrolled in a doubly randomized preference trial (DRPT) examining the treatment and treatment-preference effects between cognitive behavioral therapy and pharmacotherapy with sertraline and completed the EQ-5D and QWB-SA at baseline and 10-week post-treatment. The anchor-based methods utilized a Clinical Global Impression-Improvement (CGI-I) and Clinical Global Impression-Severity. We regressed the changes in EQ-5D and QWB-SA scores on changes in the anchors using ordinary least squares regression. The slopes (beta coefficients) were the rates of change in the anchors as functions of change in EQ-5D and QWB, which represent our estimates of MCID. In addition, we performed receiver operating characteristic (ROC) curve analysis to examine the relationship between the changes in EQ-5D and QWB-SA scores and treatment-response status. The MCIDs were estimated from the ROC curve where they best discriminate between treatment responders and non-responders. The distribution-based methods used small to moderate effect size in terms of 0.2 and 0.5 of standard deviation of the pre-treatment EQ-5D and QWB-SA scores. RESULTS: The anchor-based methods estimated the MCID ranges of 0.05 to 0.08 for the EQ-5D and 0.03 to 0.05 for the QWB. The MCID ranges were higher with the distribution-based methods, ranging from 0.04 to 0.10 for the EQ-5D and 0.02 to 0.05 for the QWB-SA. CONCLUSIONS: The established MCID ranges of EQ-5D and QWB-SA can be a useful tool in assessing meaningful changes in patient’s quality of life for researchers and clinicians, and assisting health-policy makers to make informing decision in mental health treatment. CLINICAL TRIAL REGISTRATION: Clinicaltrials.gov; Identifier: NCT00127673.